Keterampilan Menulis Puisi Melalui Teknik Brainwriting pada Siswa Sekolah Dasar - Andik Riyanto Andik Riyanto; V Teguh Suharto; Aris Wuryantoro (MAGISTRA, 2020)
This study aims todescribe the improvement of poetry writing skills with brain-writing techniques to the forth students at State Primary School 1 of Cepoko Ponorogo. This research is a Classroom Action Research (CAR) with research subjects is poetry writing skills of the fourth grade student at State Primary School 1 of Cepoko Ponorogo in two cycles. Each cycle has four components, namely planning, implementation, observation, and reflection. Research data obtained through observations and tests. The data analysis technique used comparative descriptive analysis technique. The data validity technique used in this research is triangulation technique of data collection. Results of the research reveal that improvement is measured used four aspects, namely, the accuracy of the theme and meaning, language style, diction and rhyme. Before using contextual approach and brain-writing technique the study obtained an average grade of 68. This value is below the Minimum Completeness Criteria of 75. In the first cycle, the average value was 75. Obtained 59% or 19 students had reached the Minimal Completeness Criteria (MCC). However, this percentage does not meet the achievement indicator, which is 75% or 24 students scored above the MCC. In Cycle II, the average value of writing student poetry rose to 84. Of 32 students, 27 students or 84% had achieved a minimum completeness value. It can be concluded, the target of 75% of students getting a minimum mastery value can be achieved. Thus, the application through brain-writing techniques can improve poetry writing skills of the fourth grade students at State Primary School 1 of Cepoko Ponorogo